Lost in translation? Standardising the terminology used in marine invasion biology and updating South African alien species lists. Issue 1 (22nd April 2016) - Robinson, TB; Alexander, ME; Simon, CA; Griffiths, CL; Peters, K; Sibanda, S; Miza, S; Groenewald, B; Majiedt, P; Sink, KJ
Abstract : Confusion between terms and ambiguities among definitions have long plagued the field of invasion biology. One result is disruption in flow of information from researchers to policy-makers and managers who rely on science to inform regulatory frameworks and management actions. We reviewed the South African marine biology literature to quantify the current usage of terminology describing marine invasions and found a variety of terms in use, few of which are defined when used. In response, we propose standard terminology that aligns with international practice. We then interpreted the Blackburn unified framework for biological invasions within the marine context and used this as a transparent way to apply the standardised terms to an updated list of marine alien species for the country. This resulted in the recognition of 36 alien and 53 invasive species within South Africa. Most notably, follow-up research is required to confirm the status of at least 11 listed species, the majority of which have been recorded only once, or not in the past 25 years. It is hoped that by standardising terminology, marine science in South Africa will better support authorities charged with managing the threat posed by marine alien species.